Study of some physical and chemical properties of the southern part of Al-Hawizeh Marsh/ Southern of Iraq - Saki, Safa H.; Al-Shaheen, Maitham A. (Iraqi Journal of Aquaculture, 2023)
Some physical and chemical properties of the water quality at the Al-Hawizeh Marsh Southern of Iraq were studied seasonally during the period from October 2020 to July 2021 at four stations. The studied factors included air and water temperature, pH, transparency, water salinity, electrical conductivity, dissolved oxygen, biological oxygen demand, nitrate, phosphate, silicate, and chloride ion. The results of the current study showed that the water of the southern Al-Hawizeh Marsh has high average concentrations of salinity (9.2 ppt), electrical conductivity (14.8 mS/cm), and chloride (1749.4 mg/l), as its rise to record high values ​​by a large difference from the previous local studies, and thus it is more saline than the northern part of Al-Hawizeh Marsh due to the impact of the drought extending for nine consecutive years, which threatens to change a large area in the marsh environment may lead, in the event of the continuation of the current situation of lack of water revenues and the deterioration of environmental factors of the southern Al-Hawizeh marsh, to affect the important biodiversity of this vital area.